2019
DOI: 10.1038/s41467-019-12551-5
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3K23-specific acetylation by MORF is coupled to H3K14 acylation

Abstract: Acetylation of histone H3K23 has emerged as an essential posttranslational modification associated with cancer and learning and memory impairment, yet our understanding of this epigenetic mark remains insufficient. Here, we identify the native MORF complex as a histone H3K23-specific acetyltransferase and elucidate its mechanism of action. The acetyltransferase function of the catalytic MORF subunit is positively regulated by the DPF domain of MORF (MORFDPF). The crystal structure of MORFDPF in complex with cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 55 publications
(77 reference statements)
3
59
1
3
Order By: Relevance
“…To understand how the bivalency-specific factors identified in our nucleosome pulldown assays (Figure 3D) contribute to the regulation of developmental genes at bivalent promoters in vivo, we focused on the chromatin modifying complexes SRCAP, a histone chaperone complex responsible for incorporating H2A.Z–H2B dimers into nucleosomes (Clapier et al, 2017; Giaimo et al, 2019; Mizuguchi et al, 2004), and KAT6B, a multi-subunit histone acetyltransferase that, along with its paralog KAT6A/ MOZ, has been implicated in acetylation of H3K9, H3K14, and H3K23 (Huang et al, 2016; Klein et al, 2019; Yang, 2015). Co-enrichment of several core subunits suggested recruitment of intact, functional complexes for both SRCAP (subunits DMAP1, YEATS4/GAS41, and VPS72) and KAT6B (subunits BRPF1/3, MEAF6, and ING5; Figures 3B, 3D, S3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand how the bivalency-specific factors identified in our nucleosome pulldown assays (Figure 3D) contribute to the regulation of developmental genes at bivalent promoters in vivo, we focused on the chromatin modifying complexes SRCAP, a histone chaperone complex responsible for incorporating H2A.Z–H2B dimers into nucleosomes (Clapier et al, 2017; Giaimo et al, 2019; Mizuguchi et al, 2004), and KAT6B, a multi-subunit histone acetyltransferase that, along with its paralog KAT6A/ MOZ, has been implicated in acetylation of H3K9, H3K14, and H3K23 (Huang et al, 2016; Klein et al, 2019; Yang, 2015). Co-enrichment of several core subunits suggested recruitment of intact, functional complexes for both SRCAP (subunits DMAP1, YEATS4/GAS41, and VPS72) and KAT6B (subunits BRPF1/3, MEAF6, and ING5; Figures 3B, 3D, S3A).…”
Section: Resultsmentioning
confidence: 99%
“…Given that KAT6B acetylates H3K23 (Huang et al, 2016; Klein et al, 2019; Simó-Riudalbas et al, 2015), we reasoned that the catalytic MYST domain of KAT6B might interact with a H3K27me3 mark present adjacent to H3K23. Indeed, when performing histone acetyltransferase assays with KAT6B complex purified from ESCs, KAT6B was markedly more active towards H3K27me3 nucleosomes than towards unmodified or H3K4me3-modified nucleosomes (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent study, the DPF domain of the HAT complex MOZ-related factor (MORF), was also shown to preferentially bind H3K14cr over H3K14ac. Moreover, binding of the DPF domain to H3K14cr enhanced the catalytic activity of MORF towards another acetylation site (H3K23ac), highlighting the interrelated nature of different PTMs ( Klein et al, 2019 ).…”
Section: Readers Of Histone Lys Crotonylationmentioning
confidence: 99%
“…Пока непонятно, как объяснить присутствие двух взаи- [24,25], или за счет взаимодействия других субъединиц с различными модификациями [26][27][28]. DPF-домены MOZ и MORF при этом способствуют локализации комплекса на участках с H3K14ac [12,14], а ДНК-связывающие мотивы DPF способны стабилизировать эти взаимодействия с нуклеосомой [19]. Ацетилирование H3K14 осуществляет в основном гистон-ацетилтрансфераза HBO1, которая также содержит домен MYST [29], но это могут делать и белки MOZ/MORF [30].…”
Section: Dpf взаимодействуют с ацилированными H3k14 и H3k9unclassified
“…Ацетилирование H3K14 осуществляет в основном гистон-ацетилтрансфераза HBO1, которая также содержит домен MYST [29], но это могут делать и белки MOZ/MORF [30]. Ацетилирование H3K23 и H3K9, как показано, осуществляется преимущественно с помощью MYST-домена белка MORF [31,32] и может происходить либо на данной, либо на соседней нуклеосоме [19]. Ацетилирование соседней нуклеосомы способствует изменению локализации комплекса и его перемещению на эту соседнюю нуклеосому.…”
Section: Dpf взаимодействуют с ацилированными H3k14 и H3k9unclassified